2019
DOI: 10.1007/s00426-019-01225-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mediating effect of working memory on intentional forgetting in dysphoria

Abstract: Our aim was to determine if deficits in intentional forgetting that are associated with depression and dysphoria (subclinical depression) could be explained, at least in part, by variations in working memory function. Sixty dysphoric and 61 nondysphoric participants completed a modified version of the think/no-think (TNT) task and a measure of complex working memory (the operation span task). The TNT task involved participants learning a series of emotional cue-target word pairs, before being presented with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 94 publications
(173 reference statements)
1
7
0
Order By: Relevance
“…The resulting symptoms of depressive thoughts, as discussed above, lead to the depletion of the knowledge sources of working memory and thus constitute a burden on the working memory because the difficulties facing the discoverer of happiness system in assessing environmental stimuli lead to more rumination of depressive ideas, which leads to further burden on the work of cognitive abilities. This result is consistent with the findings of Noreen et al (2020), Adams et al (2020), and Zhang et al (2018) associating depression with defective elements of working memory and confirm that depressed patients have a problem in controlling the working memory content. This result also agrees with the results of Jopling et al (2020) who show that depression affects the distribution of sources of attention associated with the central executive of working memory, and a study by Yoon et al (2014) showing that patients with depression have problems removing information unrelated to the task from the content of working memory.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The resulting symptoms of depressive thoughts, as discussed above, lead to the depletion of the knowledge sources of working memory and thus constitute a burden on the working memory because the difficulties facing the discoverer of happiness system in assessing environmental stimuli lead to more rumination of depressive ideas, which leads to further burden on the work of cognitive abilities. This result is consistent with the findings of Noreen et al (2020), Adams et al (2020), and Zhang et al (2018) associating depression with defective elements of working memory and confirm that depressed patients have a problem in controlling the working memory content. This result also agrees with the results of Jopling et al (2020) who show that depression affects the distribution of sources of attention associated with the central executive of working memory, and a study by Yoon et al (2014) showing that patients with depression have problems removing information unrelated to the task from the content of working memory.…”
Section: Discussionsupporting
confidence: 92%
“…• Reflecting a major improvement in the perception of diminished forgetting in depression and also indicating that instruction in working memory could be a promising intervention to enhance stressed people's capacity to prevent unwelcomed memories from coming to mind as supported by Noreen et al (2020).…”
Section: Discussionmentioning
confidence: 97%
“…We conducted our search in PubMed, Web of Science, and Google Scholar (on September 15, 2017) 2 , using combinations of the following Flanker. In addition, we consulted two recent review articles for additional references (Hulbert, Hirschstein, Brontë, & Broughton, 2018;Nørby, 2018), and included two studies that were published after the initial literature search had been completed (Waldhauser et al, 2018;Noreen, Cooke, & Ridout, 2019).…”
Section: Search Strategy and Inclusion Criteriamentioning
confidence: 99%
“…Interestingly, when healthy subjects affected by a mild depression (average of BDI-II score was 19.1 ± 0.6; Beck et al, 1996 [ 88 ]) were submitted to a TNT task with neutral words a deficit in suppressing no-think items appeared in these patients. Furthermore, the inability to suppress memory retrieval correlated with the BDI score [ 19 , 93 ]. A mediation analysis revealed that the relationship between the level of depressive symptoms (BDI score) in these subclinical patients and the forgetting rate was fully mediated by working memory capacity [ 93 ].…”
Section: Intentional and Incidental Forgetting In Depressionmentioning
confidence: 99%
“…Furthermore, the inability to suppress memory retrieval correlated with the BDI score [ 19 , 93 ]. A mediation analysis revealed that the relationship between the level of depressive symptoms (BDI score) in these subclinical patients and the forgetting rate was fully mediated by working memory capacity [ 93 ].…”
Section: Intentional and Incidental Forgetting In Depressionmentioning
confidence: 99%